Semiotika Rolland Barthes dalam Sampul Majalah Tempo dan Implementasinya terhadap Pembelajaran Bahasa Indonesia Kelas XII SMA - Aini, Nur; Khaerunnisa, Khaerunnisa (Universitas Muhammadiyah Surabaya, 2024)
The magazine cover of Tempo holds considerable appeal warranting in-depth examination for diverse interpretations and as a potential instructional tool. The research aims to analyze the semiotics within Tempo magazine covers, employing Roland Barthes' theory, and integrate it into Indonesian language learning, specifically for 12th-grade essay materials. Utilizing a qualitative descriptive approach, the study investigates six magazine covers to understand their denotations, connotations, and mythologies, facilitating students in drawing deeper meanings and enhancing their comprehension. By incorporating semiotic analysis into language instruction, students can develop critical thinking skills, particularly in discerning facts and opinions within essay texts. This research underscores the significance of employing visual media, such as magazine covers, to enrich language learning experiences and promote nuanced understanding of textual content.